4(2x)-3=17x+15

Simple and best practice solution for 4(2x)-3=17x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x)-3=17x+15 equation:


Simplifying
4(2x) + -3 = 17x + 15

Remove parenthesis around (2x)
4 * 2x + -3 = 17x + 15

Multiply 4 * 2
8x + -3 = 17x + 15

Reorder the terms:
-3 + 8x = 17x + 15

Reorder the terms:
-3 + 8x = 15 + 17x

Solving
-3 + 8x = 15 + 17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17x' to each side of the equation.
-3 + 8x + -17x = 15 + 17x + -17x

Combine like terms: 8x + -17x = -9x
-3 + -9x = 15 + 17x + -17x

Combine like terms: 17x + -17x = 0
-3 + -9x = 15 + 0
-3 + -9x = 15

Add '3' to each side of the equation.
-3 + 3 + -9x = 15 + 3

Combine like terms: -3 + 3 = 0
0 + -9x = 15 + 3
-9x = 15 + 3

Combine like terms: 15 + 3 = 18
-9x = 18

Divide each side by '-9'.
x = -2

Simplifying
x = -2

See similar equations:

| X^2-36=16x | | -27=-3p+5-3p | | (.7d+1)(1.5d-2)=(2.5+d)(4-1.3d) | | 2x^4=e^6 | | 0=12x^2+5x-2 | | 500-25= | | (a+b+c)x^3= | | x-15y=-3 | | 2(3x+4)=11x+6-5x+2 | | (a+b+c)3= | | 8k-6(8k-6)=116 | | 10.4+6g=24.8 | | 3(x+8)-2(x-6)=14 | | x^2+8x+4y+4=0 | | 3x-y=-9fory | | 5e-3=24 | | 6y+8=9(y-1)-3y | | b^4=125 | | D=x^3-12x | | x^2+8x-10=x | | -2(5-6p)=2p-35+5p | | 1/6x=1/18 | | x+35.6=456 | | D=2xy^2 | | 5/2x5/2 | | -6=-y+3 | | 3x+10+2x=142 | | 85=y+x | | (y^2+1)dy+(2xy+1)dx=0 | | 8-3(x-2)=32 | | 10+5c=3c | | 9x^4+6x^2-15x=0 |

Equations solver categories